2014
DOI: 10.1007/s11832-014-0596-x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of bifid iliopsoas tendon on MRI in children

Abstract: ObjectiveThe variation in the anatomy of the iliopsoas tendon is important information for orthopaedic surgeons operating around the hip. The aim of this study was to identify the prevalence of bifid iliopsoas tendons in children on magnetic resonance imaging (MRI).MethodsMRI hip and pelvis images of 50 sequential children aged 7–15 years were retrieved from our radiology database at the Evelina London Children’s Hospital from 2007 to 2013. Included were 37 children with imaging of both hips and 13 children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Crompton et al 12 studied the prevalence of bifid iliopsoas tendons on MR imaging in 87 hips in children. A bifid tendon was noted in 13 children.…”
Section: Discussionmentioning
confidence: 99%
“…Crompton et al 12 studied the prevalence of bifid iliopsoas tendons on MR imaging in 87 hips in children. A bifid tendon was noted in 13 children.…”
Section: Discussionmentioning
confidence: 99%
“…In an anatomical cadaveric study of 53 specimens by Philippon et al, two tendons were identified in 64.2% of cases, three tendons in 7.5% of cases, while a single tendon was found only in 28.3% of cases 24 . Crompton et al found a prevalence of a bifid iliopsoas tendon of 26% on MR imaging in 87 hips in children 25 . More recently, an incidence of multiple iliopsoas tendons of 18% during endoscopic transcapsular release have been reported 26 .…”
Section: Discussionmentioning
confidence: 99%
“…A few things are important to keep in mind while performing iliopsoas release. Re-cent studies showed that a multiple iliopsoas tendon may exists in a large number of patients 6,29 . Philippon et al 9 in a cadaveric study found that the iliopsoas tendon was composed by two tendons in 64.2% of cadavers, by three tendons in 7.5% of cases and a single tendon in only in 28.3% of cases.…”
Section: Discussionmentioning
confidence: 99%